h - Ebrahim, Zeinab K. (2018)
This study was done to determine the impact of gastrointestinal parasites infestation on some hematological and biochemical parameters in sheep. 25 adult sheep, of both sex aging 1-1.5 years old and average 50 kg body weight are used. These animals were divided into two groups according to fecal examination. Group 1 contained 9 sheep were apparently healthy and free from internal parasites and they were used as a control group. Group 2 contained 16 sheep and these sheep were naturally infested with gastrointestinal nematodes and clinically were suffered from emaciation, reduced growth rate, anemia, diarrhea and pale mucosa. Blood samples from both groups were collected and analyzed for hematological parameters (Hb, PCV, RBCS and total WBCs count) and some biochemical parameters ( total protein, albumin, globulin, glucose, AST, ALT, BUN , creatinine , calcium, iorganic phosphorus, magnesium, sodium, potassium and iron). Our results revealed that there were a significant decrease in Hb, PCV and RBCS values , while total leucocytic count was significantly increased in infested group than in healthy one . Biochemical analysis showed a significant decrease in serum total protein, albumin, glucose , BUN, calcium, inorganic phosphorus , iron and a significant increase in serum AST and ALT in infested group as compared with the control group, while there were non-significant changes in values of serum globulin , creatinine, magnesium, sodium and potassium between infested and control ones.
Includes references.
Summary in Arabic
Keywords: Sheep -- Diseases -- Diagnosis; Sheep -- Parasites